How do the various media types and vape shops impact the perception of e-cigarettes use and harm in Malaysia? - Wee, Lei Hum; Chan, Caryn Mei Hsien; Tee, Guat Hiong; Draman, Samsul; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Ho, Bee Kiau; Md Haris Robson, Noor Zurani; Nik Mohamad, Mohamad Haniki; Ab Rahman, Jamalludin (Malaysia Medical Association, 2017)
The popularity of e-cigarettes over conventional cigarettes is important to examine e-cigarette perceptions as to some why current cigarette smokers make a switch, while some do not. The objective of this study is to examine current smokers' perceptions on e-cigarette use following exposure to information derived from media and vape shop messages promoting its use and harm. Methods: The current cross-sectional study is part of a national prevalence study on electronic cigarettes. The focus of this paper is on the perceptions of current adult male smokers towards e-cigarettes. A total of 922 male current smokers (smoking conventional cigarettes and /or e-cigarettes) aged 18 years and above were recorded using face-to-face interviews. Logistic regression was used to examine the association between media exposure and e-cigarette perceptions. Results: About half of the respondents were within the age 25 - 44 years old. About one third of the respondents reported they had ever-used electronic cigarettes (29.1%). Current male smokers who visited a vape shop and exposed to information about the dangers of smoking e-cigarette were four times more likely to perceive that people reacted more positively to e-cigarettes users than that to tobacco smokers (OR=4.09; p=0.011; CI=1.38-12.12). Current smokers who are exposed to social media or the internet in both messages promoting the use of e-cigarettes and about the harmfulness of the use are more likely to perceive that the urge to smoke is reduced by using e-cigarettes (OR=1.66; p=0.013; CI=1.112.49; OR=1.65; p=0.015; CI=1.10-2.48) respectively. Discussion: Finding from this study presents one of the first ever to identify the different types of media influencing the perceptions of current smokers on e-cigarettes use in Malaysia.